Status of Teacher Professional Development (TPD) at Secondary Level Schools - Poudel, Ambika Prasad (Rupantaran: A Multidisciplinary Journal, 2024)
Education reform and the pursuit of quality education are common concerns among stakeholders showing their concern to educational development. In recent years, Teacher Professional Development (TPD) has emerged as a pivotal component for advancing education reform efforts and bolstering educational quality. This article attempts at describing the existing TPD status of the secondary level schools in Nepal. In the study, the headmasters of the four selected secondary level schools were the informants; and a survey checklist was used as the research tool to collect required data. The data were analyzed and interpreted using descriptive statistics. The study found that the secondary schools were quite poor regarding their performance of TPD related activities, most of them had weak TPD status. This finding led to conclude that the concerned authorities need to be more responsible to make improvements in the existing TPD situation at the secondary schools in Nepal.